Analisis Komunikasi Publik Dakwah Qotrunnada Syathiry Melalui Media Sosial Di Tiktok Berdasarkan Teori Komunikasi Massa Harold D. Lasswell - Altruis Bizurai Chillyness (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the public communication of dakwah (Islamic preaching) carried out by Qotrunnada Syathiry through the social media platform TikTok, based on Harold D. Lasswell's mass communication theory. The research explores how Qotrunnada Syathiry utilizes TikTok to disseminate dakwah messages and engage with a broader audience, focusing on the five key elements of Lasswell's model: who (the communicator), what (the message), in which channel (the medium), to whom (the audience), and with what effect (the impact). By employing content analysis and examining the interaction metrics such as views, likes, comments, and shares, the study reveals that Qotrunnada's communication approach effectively builds credibility (ethos), evokes emotional responses (pathos), and utilizes TikTok's interactive features to engage audiences. The findings indicate that TikTok serves as an efficient medium for reaching diverse audiences, especially the younger generation, while promoting positive values and spiritual messages. This research contributes to the understanding of how mass communication theory can be applied to digital platforms for effective dakwah and offers insights for future research in digital Islamic communication strategies.